Graphical Enhancements for Voice Only Conference Calls - Colburn, R. Alex; Cohen, Michael; Drucker, Steven; Gupta, Anoop; LeeTiernan, Scott; Counts, Scott (2001)
We present two very low bandwidth graphically enhanced interfaces for small group voice communications. One interface presents static images of the participants that highlight when one is speaking. The other interface utilizes three-dimensional avatars that can be quickly created. Eleven groups of 4 or 5 people were presented with each enhanced interface as well as conducting a live conversation and a voice only conversation. Experiments show that both graphically enhanced interfaces improve the understandability of conversations, particular with respect to impressions that others in the group could express themselves more easily, knowing who is talking, and when to speak. Little difference was found between the two graphical interfaces. Analysis of voice tracks also revealed differences between interfaces in the length and number of medium duration silences.